Effect of magnesium sulfate on bleeding time in pregnancy - Z Khakbazan; A Alishirzad; A Mirnateghie; Gh Babaei; M khakbazan (Tehran University of Medical Sciences, 2005)
Introduction: According to some studies, pharmacological concentrations of Mg2+ have anti-thrombotic effects and interfere with platelet aggregation in vitro and in vivo. Materials and Methods: The study group consisted of 50 pregnant women who required magnesium sulfate for mild pre-eclampsia or preterm labor. In all patients, a platelet count, magnesium level, bleeding time and mean arterial pressure were obtained before and 2 hours after magnesium sulfate infusion. Magnesium sulfate was started with a 6 gr intravenous bolus, followed by 2 gr/hr infusion. Bleeding time was measured by Duke method. Data were analyzed with Mann Whitney U and Wilcoxon rank tests. Results: Thirty one patients (62%) received magnesium sulfate for preterm labor and 19 (38%) for mild pre-eclampsia. Analysis of the entire study group revealed a rise in the magnesium level (p<0.0001), a lowering of the mean arterial pressure (p<0.0001) and no significant difference of the bleeding time and platelet count. Comparison of platelet count, magnesium level and bleeding time before and 2 hours after magnesium sulfate infusion revealed no significant difference in two groups. Conclusion: According to this study, magnesium sulfate with usual dosage has no effect on bleeding time in pregnancy.